(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Non-compliance is one of the major reasons of CL related complications. Various research studies have been done over the past three decades to find reasons for patient non-compliances. Use of CLs over the recommended replacement schedule has been one of the major reasons leading to CLs complications. It is evident that the CLs user are often unaware of their non-compliance towards lens care and maintenance regimen. Even after introduction of daily disposable lenses and one-step multipurpose solution non-compliance towards CLs use is still a major problem in CLs patients. The complications due to patient noncompliance can be sometimes irreversible. This research will help us understand CL user reasons of intentionally or unintentionally being non-compliant to recommended replacement frequency. Method: All CL users willing to share their experience participated in this questionnaire based online survey which was designed with the help of focused group discussion. Results: Most of the CL wearer prefer buying pairs for at least 6 months at a time. Almost 80% of CL wearers do not replace their CL as per MRRF. 70% of those who participated wore CL for more than 10 hours per day. The male and female ratio is almost equal in the participants participated in the research. Conclusion: Research done in the past suggest incomplete knowledge imparted to the wearer or CL forgetting the instructions given to them at dispensing. Research also suggest some CL wearer knowingly are non-compliant to MRRF. This study tries to find loopholes in a CL practice by finding reasons of non-compliance as per CL wearers prospective and probable suggestion from the user itself. An ECP is a paramedical person who has the right to prescribe them, whether according to MRRF or as per their knowledge of the patient’s ocular status. For e.g., an antibiotic medicine is supposed to be prescribed for 3 days or 5 days, once or twice is decided by the medical practitioner prescribing. As this research shows over 50% of the CL wearer said that their 'ECP said its okay'.